Impact of Xenogeneic Silencing on Phage–Host Interactions. Issue 23 (22nd November 2019) - Pfeifer, Eugen; Hünnefeld, Max; Popa, Ovidiu; Frunzke, Julia
Abstract: Phages, viruses that prey on bacteria, are the most abundant and diverse inhabitants of the Earth. Temperate bacteriophages can integrate into the host genome and, as so-called prophages, maintain a long-term association with their host. The close relationship between host and virus has significantly shaped microbial evolution and phage elements may benefit their host by providing new functions. Nevertheless, the strong activity of phage promoters and potentially toxic gene products may impose a severe fitness burden and must be tightly controlled. In this context, xenogeneic silencing (XS) proteins, which can recognize foreign DNA elements, play an important role in the acquisition of novel genetic information and facilitate the evolution of regulatory networks. Currently known XS proteins fall into four classes (H-NS, MvaT, Rok and Lsr2) and have been shown to follow a similar mode of action by binding to AT-rich DNA and forming an oligomeric nucleoprotein complex that silences gene expression. In this review, we focus on the role of XS proteins in phage–host interactions by highlighting the important function of XS proteins in maintaining the lysogenic state and by providing examples of how phages fight back by encoding inhibitory proteins that disrupt XS functions in the host. Sequence analysis of available phage genomes revealed the presence of genes encoding Lsr2-type proteins in the genomes of phages infecting Actinobacteria. These data provide an interesting perspective for future studies to elucidate the impact of phage-encoded XS homologs on the phage life cycle and phage–host interactions. Graphical abstract: Unlabelled Image Highlights: The activity of phages represents a major driver of horizontal gene transfer. Xenogeneic silencing (XS) plays an important role in the silencing of foreign DNA. XS proteins shape (pro-)phage–host interaction. Phages employ multiple mechanisms to counteract XS. Genome analysis revealed that actinophages encode different types of Lsr2-like proteins.